An integrated shoelace–power law preprocessing workflow for supporting ship-specific wind load assessment during berthing - Liang Ma; Yanru Han; Yuanyuan Chen; Zhenkai Huang; Yu Zhang; Liang Cao; Jianing Dan; Zhaorui Li (Frontiers in Marine Science, 2026)
Wind loads are critical safety concerns for ship berthing and mooring operations in ports. Existing standard methods for wind load assessment often adopt simplified geometric assumptions and fixed wind shear parameters, lacking ship-specific and loading-adaptive capabilities which hinders the practical implementation of the One Ship One Calculation (OSOC) concept in ship wind load assessment. This study proposes an integrated Shoelace-Power Law Model (S-PLM) as a preprocessing workflow for ship windage geometry analysis and height-consistent equivalent wind speed estimation. The workflow combines polygon area calculation via the shoelace algorithm, loading-dependent geometric centroid calculation, and power-law-based vertical wind speed conversion. Validation against the OCIMF standard method shows better agreement in windage area (MAPE = 0.63%) and acceptable deviations in equivalent wind speed across different vessels and loading conditions. Sensitivity analysis of the power-law exponent (α = 0.10–0.25) confirms controllable parameter influence on model outputs. The proposed S-PLM provides reliable, ship-specific preprocessing inputs for subsequent wind load evaluation, supporting refined operational risk assessment during berthing.